(untitled) (Journal of the College of Basic Education, 2022)
The research aims to determine the effectiveness of using (Infographics) in self-learning skills for fifth-grade students and to verify the research objective. There is no statistically significant difference at the level (0.05) between the average scores of the experimental group of students who will study using the infographic and the average scores of the control group who will study according to the usual method in the self-learning skills scale. The experimental design with partial control was chosen for the two experimental and control groups, each with a post-test to test the acquisition of a self-learning skills scale. The research community is represented by all students of the fifth scientific grade in preparatory and secondary schools for boys, governmental daytime affiliated to the Maysan Education Directorate, as the number of students reached 4513-students distributed to (41- preparatory & secondary) schools, and the research sample was chosen by the simple random method (lottery). (4.) In Sada Al-Taf Secondary School for Boys, it contained 60 students distributed in two divisions for the fifth applied scientific grade, with 30 students in each division, and by simple random assignment; Division (B) represented the experimental group that will be studied using infographics; and the same Division (A) represented the control group which will be studied in the usual way . The experimental and control groups were rewarded for intelligence, previous achievement, and a measure of self-learning skills. The research tools were prepared The Self-Learning Skills Scale consisted of 34 items divided into five skills (goal-setting and planning skills, organizational skills, guidance and control skills, learning resource management, and self-evaluation skills), answered on a five-year Likert scale (always, often, sometimes, seldom, never). Where the validity and reliability of the scale were tested by using the split-half method and its equation with the Spearman-Brown equation, which amounted to (0.79), and the psychometric properties were extracted. The experiment was applied in the first semester and lasted (11) weeks, and (23) daily teaching plans were prepared for the experimental group using infographics, and the same for the control group according to the usual method. After completing the application of the experiment, the data were treated statistically by relying on the statistical package (SPSS). The results showed that the experimental group who studied using the infographic in the learning skills scale outperformed their peers in the control group with significant significance and a large effect size. In accordance with the study findings, the researcher advises the use of infographics as an alternative to the traditional style of education.